# Given that f(x)=3x^2 - 2x + 5 and g(x) =3x - 1, how do you find g(4) - f(-2)?

### 2 Answers | Add Yours

We are given that f(x) = 3x^2 - 2x + 5 and g(x) = 3x - 1.

We have to find g(4) - f(-2).

g(4) = 3*4 - 1 = 12 - 1= 11

f(-2) = 3*(-2)^(2) - 2*(-2) + 5 = 3*4 + 4 + 5 = 12 + 4 + 5 = 21

Therefore g(4) - f(-2) = 11 - 21 = -10

**The required value of g(4) - f(-2) is -10.**

Given f(x) = 3x^2-2x+5 and g(x) = 3x-1.

To find g(4)- f(-2).

To get f(-2) we put x = -2 in f( x) = 3x^2-2x+5. Then f(-2) = 3(-2)^2-2(-2) +5 = 3*4+2*2+5 = 12+4+5 = 21.

To gget g(4) we put x = 4 in g(x) = 3x-1 . Then g(4) = 3*4-1 = 12-1 = 11.

Therefore g(4) = 11. f(-2) = 21.

So g(4) - f(-2) = 11-21 = -10.

**Therefore g(4) - f(-2) = -10.**